RNF5 inhibits HBV replication by mediating caspase-3-dependent degradation of core protein - Xu, Jing; Song, Hongxiao; Xu, Fengchao; Gao, Yanli; Jiang, Hongyu; Tan, Guangyun (Frontiers in Microbiology, 2025)
The RING finger protein 5 (RNF5), an E3 ubiquitin ligase, has demonstrated significant antiviral activity against various viruses, including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Kaposi’s sarcoma-associated herpesvirus (KSHV). However, its role in hepatitis B virus (HBV) replication has not been previously studied. In this study, we demonstrate that RNF5 effectively inhibits HBV replication by promoting the degradation of the HBV Core protein through a Caspase-3-dependent pathway. We first show that RNF5 expression is upregulated in HBV-infected cells and patient samples, suggesting a role in the host’s antiviral response. Subsequently, we investigate the mechanism by which RNF5 mediates its antiviral effect, finding that RNF5 targets the Core protein for degradation independently of its E3 ubiquitin ligase activity. The degradation of Core protein is mediated through a Caspase-3-dependent mechanism rather than the proteasomal pathway. Interestingly, RNF5’s antiviral function does not rely on ubiquitination, indicating an alternative pathway involving apoptosis-related processes. These findings highlight the multifunctional role of RNF5 and suggest that targeting RNF5 could serve as a novel therapeutic approach to control HBV replication, providing new insights into the development of antiviral therapies against HBV.